1971
DOI: 10.1002/cber.19711040125
|View full text |Cite
|
Sign up to set email alerts
|

Mikrobiologische 11β‐Hydroxylierung von 3β‐Hydroxy‐5α.6α‐epoxy‐steroiden

Abstract: HEine Reihe von 3P-Hydroxy-5x.6x-epoxy-stero~~len wird niit dem Pilz Curiwlurirr I/nirrlu ohne Bildung voii Nebenprodukten spezitisch in 11IJ-Stellung hydroxylicrt.Microbiological 11 P-Hydror ylation of 3P-Hydroxy-5a.6a-epoxgsteroids Some 3~-Hydroxy-5x,6a-epoxysteroids ore hydroxylated specitically in I I (?-position without formation of by-products by the fiingris Cnrrnlnri(r lnnutcr.Die niikrohiologische Einfiihrung einer Hydroxylgruppe in die 1 I :f-Stellung eines Steroids wird stets von Hydroxylierungen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1971
1971
1979
1979

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Microbial transformations of epoxy steroids have not been extensively studied, although dehydrogenation (14), C-11 hydroxylation (15,16) and ring opening (17) have been reported. In analogy with earlier work (17), we found that 4a is opened nonenzymically to the 6a-hydroxy-A4-3-ketone lc.…”
mentioning
confidence: 99%
“…Microbial transformations of epoxy steroids have not been extensively studied, although dehydrogenation (14), C-11 hydroxylation (15,16) and ring opening (17) have been reported. In analogy with earlier work (17), we found that 4a is opened nonenzymically to the 6a-hydroxy-A4-3-ketone lc.…”
mentioning
confidence: 99%